2019
DOI: 10.1002/jcp.29307
|View full text |Cite
|
Sign up to set email alerts
|

AMPK‐mTOR‐ULK1 axis activation‐dependent autophagy promotes hydroxycamptothecin‐induced apoptosis in human bladder cancer cells

Abstract: 10-hydroxycamptothecin (HCPT), a natural plant extract, exerts anticancer capacity.HCPT has been reported to induce apoptosis and autophagy in human cancer cells.The interaction between autophagy and apoptosis induced by HCPT and the molecular mechanism in bladder cancer cells were investigated in this study. Our results confirmed that HCPT suppressed cell viability and migration and caused cellcycle arrest in T24 and 5637. Then, we used Z-VAD(OMe)-FMK to clarify that apoptosis induced by HCPT was mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…As noted herein, ULK1 plays an important role in the initiation of autophagy [206]. The induction of protective autophagy to inhibit apoptosis is one of the reasons for the development of drug resistance in tumor cells during therapy [207].…”
Section: Small Molecule Drugs Targeting Ulk Reverse Tumor Resistancementioning
confidence: 92%
“…As noted herein, ULK1 plays an important role in the initiation of autophagy [206]. The induction of protective autophagy to inhibit apoptosis is one of the reasons for the development of drug resistance in tumor cells during therapy [207].…”
Section: Small Molecule Drugs Targeting Ulk Reverse Tumor Resistancementioning
confidence: 92%
“…MiR-139-5p targets Bmi-1 which induces reversion of invasion and migration [ 76 ]. Hydroxycamptothecinals initiated apoptosis via promoting AMPK/mTOR pathway dependent apoptosis [ 77 ], but the exact involvement of miRNAs in this process is not yet known.…”
Section: Mirna-mediated Regulation Of Mtor In Bladder Cancermentioning
confidence: 99%
“…On the other hand, activation of AMPK can also negatively interfere with cancer cells either by arresting cell growth or by priming cancer cells to be more sensitive to death signals 53 . This latter effect is usually linked to an AMPK-dependent inhibition of mTOR 53,54 , which is involved in another survival pathway within many cells 54 . However, in the current work, we found that the mTOR pathway is also activated upon treatment with SA or ASA.…”
Section: Discussionmentioning
confidence: 99%